2019
DOI: 10.21273/hortsci13703-18
|View full text |Cite
|
Sign up to set email alerts
|

Model Simulation of Cucumber Yield and Microclimate Analysis in a Semi-closed Greenhouse in China

Abstract: Adequate greenhouse environmental management is very important for improving resource use efficiency and increasing vegetable yield. The objective of this study was to explore suitable climate and cultivation management for cucumber to achieve high yield and build optimal yield models in semi-closed greenhouses. A fruit cucumber cultivar Deltastar was grown over 4 years in greenhouse and weekly data of yields (mean, highest and lowest) and environmental variables, including total radiation, air tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Assuming that temperature and radiation are the most important variables for heterogeneous microclimates within the green-house, [26] showed that optimized re-arrangement of pots can reduce accumulated positional effects by 90%. Second, for a fixed-position arrangement, this information can be used as a covariate [7, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that temperature and radiation are the most important variables for heterogeneous microclimates within the green-house, [26] showed that optimized re-arrangement of pots can reduce accumulated positional effects by 90%. Second, for a fixed-position arrangement, this information can be used as a covariate [7, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regression models have been successfully utilized in the prediction of yield losses caused by multiple diseases and climatic conditions in crops like wheat (Jevtic et al, 2017;Ficke et al, 2018;Jevtic et al2020), French bean (Kumar and Kudada, 2018), cucumber (Ding et al, 2019), bitter gourd (Prasanth et al, 2019), potato (Yellareddygari et al, 2018) to name a few. Multiple linear regression using yield as dependent variable and GSB and powdery mildew intensities as independent variables was conducted.…”
Section: Regression Analysismentioning
confidence: 99%
“…e detailed information of the experimental greenhouse can be referenced in Ding et al [2]. Mini-cucumbers (Cucumis Sativus L. cv.…”
Section: Field Experiments and Measurement On Plantsmentioning
confidence: 99%
“…With the promotion and application of semiclosed greenhouses in China, the excess solar energy in summer was collected and stored, and this energy should be reused to heat the greenhouse in winter [1]. As a result, the impact of low temperature in winter on yield has been greatly improved [2]. Nevertheless, in greenhouses without supplementary light, low light intensity remains an important cause affecting winter production [1].…”
Section: Introductionmentioning
confidence: 99%